Microstructure and properties of UNS S32750 super-duplex stainless steels processed by hot isostatic pressing - SHANG Feng; WANG Zhi-yong; QIAO Bin; HE Yi-qiang; LI Hua-qiang (Fenmo yejin jishu)
The UNS S32750 super-duplex stainless steels were prepared by plasma rotating electrode processing and hot isostatic pressing in this study. The microstructure and mechanical properties of the steels before and after the solution treatment were investigated by optical microscope (OM), scanning electron microscope (SEM), electron back scattering diffraction (EBSD), and electronic material testing machine. The results indicate that the UNS S32750 super-duplex stainless steel powders prepared by plasma rotary electrode processing can be densified by hot isostatic pressing sintering at 1200 ℃ for 3 h at 150 MPa, and the relative density of the sintered parts is 99.7%. The σ phases precipitate in the sintered parts during the furnace slow cooling process, significantly undermining the impact toughness. In contrast, the σ phases are dissolved completely after the solution treatment at 1035 ℃ for 1 h followed by the water quenching, leading to a notable increase in the impact toughness. A duplex structure of the α and γ phases is identified, which significantly affects the properties of the specimens. In detail, the volume ratio between the α and γ phases is 65:35, the tensile strength and yield strength of the specimens are 791 MPa and 586 MPa, respectively, the elongation is approximately 38%, and the impact absorbing energy is 236 J.